Octant Degeneracy and Quadrant of Leptonic CPV Phase at Long Baseline ν Experiments and Baryogenesis - Kalpana Bora; Gayatri Ghosh; Debajyoti Dutta (Advances in High Energy Physics)
In a recent work by us, we have studied how CP violation discovery potential can be improved at long baseline neutrino experiments (LBNE/DUNE), by combining with its ND (near detector) and reactor experiments. In this work, we discuss how this study can be further analysed to resolve entanglement of the quadrant of leptonic CPV phase and octant of atmospheric mixing angle θ23, at LBNEs. The study is done for both NH (normal hierarchy) and IH (inverted hierarchy), HO (higher octant), and LO (lower octant). We show how baryogenesis can enhance the effect of resolving this entanglement and how possible values of the leptonic CP violating phase δCP can be predicted in this context. With respect to the latest global fit data of neutrino mixing angles, we predict the values of δCP for different cases. In this context we present favoured values of δCP (δCP range at ≥2σ) constrained by the latest updated BAU range and also confront our predictions of δCP with an up-to-date global analysis of neutrino oscillation data. We find that some region of the favoured δCP parameter space lies within the best fit values around δCP≃1.3π–1.4π. A detailed analytic and numerical study of baryogenesis through leptogenesis is performed in this framework within the nonsupersymmetric SO(10) models.